Routledge handbook of the influence industry - Briant, Emma; Bakir, Vian, 1971- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This Handbook provides the first comprehensive examination of the influence industry and how it operates worldwide across different domains. The rapid evolution of emerging technologies and data-driven persuasive practices has been linked to the spread of misleading content in domestic and foreign influence campaigns. This has prompted worldwide public and policy discussions about disinformation and how to curb its spread. However, less attention has been paid to the increasingly data-driven commercial industry taking advantage of the opportunities these new technologies afford. The handbook uses the term 'influence' here to include not only messaging and public relations (PR), which fell within the traditional focus of propaganda studies, but to consider the infrastructure and actors behind an advanced array of capabilities that can be used in a coordinated way to affect an audience's emotions, ideas, and behaviors in order to advance a state or non-state actor's objectives - increasingly based on data-driven profiling. The volume fills a gap in scholarship exploring the recent technical, political and economic development of this industry, surveying the extent of different technologies and services offered to clients worldwide across multiple domains (commercial, political, national security and government). The chapters are divided into three thematic sections, and evaluate Influence Industry practices, aims and effectiveness across audiences; business practices and economics; and democratic structures and human rights. They also offer advice for researchers and consider key ethical issues and new regulatory approaches. This volume will be of much interest to students of political science, propaganda studies, sociology, communication studies and journalism"--
Keywords: Propaganda; Public relations; Social influence; Digital media -- Political aspects; POLITICAL SCIENCE / Political Process / Political Advocacy